Born of resistance : cara a cara encounters with Chicana/o visual culture - Baugh, Scott L.; Sorell, V. A. (Victor A.) (The University of Arizona Press, 2015)
"This collection of essays gives voice to a diversity of perspectives involved in the production, exhibition, documentation, and interpretation of landmark Chicana/o visual cultural expression since the 1960s, exploring the idea of resistance, with a unifying theme that all art is political; artwork discussed includes etching, lithography, digital retablos, wooden sculpture, photography, painting, video installation, and documentary film"--Provided by publisher.